Climate change, migration, and health: Development of a case-based workshop for immigrant and refugee health professionals - Eleanor H. Emery; Tess Wiskel; Kimberly Humphrey; Gaurab Basu (The Journal of Climate Change and Health)
Introduction: Climate change is contributing to unprecedented levels of migration with complex impacts on the health of displaced populations. Immigrant and refugee health professionals are well positioned to understand the issues at the intersection of climate change, forced migration, and health, and to participate in the development of solutions to this crisis. However, little has been done to equip these professionals to join the dialogue around climate change. Materials and Methods: We developed an interdisciplinary, case-based workshop to introduce refugee and immigrant health professionals at an international conference to the ways in which climate change is impacting the health of the communities they serve. We employed a community organizing approach to show participants how their existing skills, knowledge base, and networks can be used to identify and mitigate climate impacts. Results: The workshop was attended by approximately fifty participants. In a post workshop survey, sixty percent of participants agreed with the statement that the workshop would change their professional work, and there was a significant increase both in those who reported that they understood how climate change impacts immigrant communities and in how to use their relationships and resources to combat climate change. Discussion: The discussion themes illustrated the breadth of knowledge of participants, especially regarding the social determinants of health, the health inequities that shape climate vulnerability, and myriad problem-solving processes. Conclusion: This workshop offers one model for how a brief educational intervention using case-based learning and the tenets of community organizing can be used to introduce a new community of providers to climate change work.